Congenital partial pericardial defect confirmed based on spontaneous pneumothorax: A case report and literature review. (2020) - Date, Naoki; Komatsu, Teruya; Fujinaga, Takuji
Highlights: Congenital partial pericardial defects are rare but can cause cardiac herniation. Pneumopericardium combined with pneumothorax suggests pericardial defect. Pneumothorax may worsen the heart protruding through the pericardial defect. VATS should be considered in the patients with a pericardial defect. Abstract: Introduction: Congenital pericardial defects are rare but can cause fatal complications. Most cases are asymptomatic and incidentally detected during a thoracic surgery or autopsy. We report a case of a partial pericardial defect confirmed based on spontaneous pneumothorax. Presentation of case: A 16-year-old boy with left spontaneous pneumothorax showed pneumopericardium on chest X-ray. Chest computed tomography revealed a partial pericardial defect. Video-assisted thoracoscopic surgery was performed, and a small pericardial defect was confirmed at the level of the upper pulmonary hilum. We did not reconstruct the defect because of the improbability of cardiac herniation. Discussion: Pneumopericardium combined with pneumothorax suggests the existence of a pericardial foramen. Partial pericardial defects could cause cardiac herniation or strangulation, and pneumothorax may worsen the protruding of the heart. Video-assisted thoracic surgery is an effective method to prevent the recurrence of pneumothorax and determine whether reconstruction of the defect is required. Conclusion: Video-assisted thoracic surgery should be performed in the case of a pericardial defect combined with pneumothorax.